Inositol 1,4,5‐Trisphosphate Receptors in Endothelial Cells Play an Essential Role in Vasodilation and Blood Pressure Regulation - Qingsong Lin; Lingyun Zhao; Ran Jing; Christa Trexler; Hong Wang; Yali Li; Huayuan Tang; Fang Huang; Fei Zhang; Xi Fang; Jie Liu; Nan Jia; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2019)
Background Endothelial NO synthase plays a central role in regulating vasodilation and blood pressure. Intracellular Ca2+ mobilization is a critical modulator of endothelial NO synthase function, and increased cytosolic Ca2+ concentration in endothelial cells is able to induce endothelial NO synthase phosphorylation. Ca2+ release mediated by 3 subtypes of inositol 1,4,5‐trisphosphate receptors (IP3Rs) from the endoplasmic reticulum and subsequent Ca2+ entry after endoplasmic reticulum Ca2+ store depletion has been proposed to be the major pathway to mobilize Ca2+ in endothelial cells. However, the physiological role of IP3Rs in regulating blood pressure remains largely unclear. Methods and Results To investigate the role of endothelial IP3Rs in blood pressure regulation, we first generated an inducible endothelial cell–specific IP3R1 knockout mouse model and found that deletion of IP3R1 in adult endothelial cells did not affect vasodilation and blood pressure. Considering all 3 subtypes of IP3Rs are expressed in mouse endothelial cells, we further generated inducible endothelial cell–specific IP3R triple knockout mice and found that deletion of all 3 IP3R subtypes decreased plasma NO concentration and increased basal blood pressure. Furthermore, IP3R deficiency reduced acetylcholine‐induced vasodilation and endothelial NO synthase phosphorylation at Ser1177. Conclusions Our results reveal that IP3R‐mediated Ca2+ release in vascular endothelial cells plays an important role in regulating vasodilation and physiological blood pressure.